(untitled) (Principles of Medical Toxicology, 2025)
Author Mrs. Bhagyamma Tholla, Assistant Professor, Department of Pharmacology, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, India Abstract Medical toxicology has evolved from ancient observations of poisonous substances to a sophisticated medical specialty addressing diverse toxic exposures. Its origins trace back to Egyptian, Greek, and Roman civilizations, with significant advancements marked by Paracelsus's principle that "the dose makes the poison." The discipline encompasses the study, diagnosis, management, and prevention of adverse effects from medications, occupational chemicals, environmental toxins, and biological agents. Core principles include dose-response relationships, routes of exposure, mechanisms of action, and systematic approaches to risk assessment. Medical toxicologists serve crucial roles across healthcare settings—managing poisonings in emergency departments, providing consultation for complex cases, conducting surveillance of emerging threats, advising on pharmaceutical safety, and contributing to environmental and occupational health policies. The field continues to adapt to contemporary challenges including novel pharmaceuticals, designer drugs, environmental pollutants, and chemical threats. This multidisciplinary specialty bridges clinical medicine, pharmacology, biochemistry, and public health to address the increasing complexity of toxic exposures in modern society. Keywords: Medical Toxicology, Poisoning, Toxic Exposure, Paracelsus, Risk Assessment VIEW PDF